Effect of steam explosion on nutritional components, physicochemical and rheological properties of brown rice powder - Kong, Feng; Zeng, Qinghua; Li, Yue; Di, Xue; Ding, Yishuai; Guo, Xingfeng (Frontiers in Nutrition, 2022)
Brown rice powder is underutilized mainly due to its lower starch digestibility and poor processing performance. The present study investigated the potential of steam explosion on the improvement of nutritional and physicochemical characteristic in brown rice powder and rheological property of paste. Compared with native brown rice powder, steam explosion at 0.5 MPa for 7 min increased the water-extractable arabinoxylans (5.77%), reducing sugar content (21.04%) and iodine blue value (30.38%), which indicated steam explosion destroyed the intact cells of brown rice. And the crystalline structure of brown rice powder was destroyed into an amorphous structure by steam explosion. Steam explosion enhanced the degree of gelatinization (4.76%~351.85%) and solvent retention capacity of brown rice powder, compared with native sample. The effect on the intact cells and starch structure of brown rice caused the starch digestibility enhancement remarkable. Viscoelastic profiles confirmed that steam explosion weakened the paste strength and elasticity corresponded with hardness and cohesiveness by increasing the loss factor (tanδ). This work provided important information for brown rice powder modified by steam explosion (0.5 MPa, 7 min) with good nutritional property (nutrients and digestibility) and processability (solvent retention capacity, textural and rheological property). Steam exploded brown rice powder (0.5 MPa, 7 min) could serve as a potential ingredient widely used in food products.